Compartment syndrome as a novel complication of extended spectrum beta lactamase Escherichia coli necrotising soft tissue infection – A case report. (October 2022) - Gibson, Damien; Chow, Oliver; Seth, Ishith; Siu, Adrian Hang Yue; Kwei, Johnny
Abstract: Introduction and importance: Necrotising soft tissue infections (NSTI) encompass a group of destructive soft tissue disease processes which can involve skin, subcutaneous tissue, fascia and or muscle, associated with rapid spread along tissue planes and mortality. Clinical presentations include progressive pain, suppuration/necrosis and systemic toxicity with haemodynamic instability. While diagnosis is based on clinical findings it can be augmented with imaging. Treatment is typically in the form of resuscitation, immediate administration of broad spectrum intravenous antibiotics and urgent source control through radical surgical debridement. Case presentation: An 82-year-old man presented with left forearm/hand pain and fevers in the context of immunocompromise. Examination found tense swelling of the left volar and dorsal forearm and hand, absent distal pulses with pain and paraesthesia over both surfaces. He underwent surgical debridement with fasciotomy and remained in intensive care with blood cultures revealing ESBL E. coli . Clinical discussion: Compartment syndrome is a rare complication of NSTI and its clinical presentation can obscure early diagnosis. ESBL E. coli is an uncommon pathogen to cause monomicrobial infection and must be accounted for when considering broad spectrum empirical antibiotic cover. Conclusion: Review of this case and the literature show a rare presentation of NSTI and highlights the importance of early diagnosis based on even a small index of suspicion. It also shows the key significance rationalisation of antibiotics as soon as practicable, given that even broad spectrum empirical cover can be inappropriate in the context of novel microorganisms, particularly in high risk patients. Highlights: First recorded case of monomicrobial ESBL E. coli compartment syndrome ESBL E. coli NSTI is rare and not covered by many empirical antimicrobial guidelines. Compartment syndrome secondary to NSTI is uncommon and associated with streptococci. Early recognition and prompt management are essential to prognosis.